A Dual‐band and dual‐polarized antenna array for 2G/3G/LTE base stations. Issue 2 (28th October 2015) - Zhang, Xiaoyan; Yang, Gao; Wang, Xueren; Li, Bincheng
ABSTRACT: A dual‐band antenna array is proposed for the application of base station (BS) in 2G/3G/long term evaluation (LTE) mobile communications. This antenna consists of two independent ±45° dual‐polarized arrays, one of which operates from 1.71 to 2.17 GHz, and the other of which is designed from 2.5 to 2.69 GHz. The proposed BS antenna array has a high isolation of greater than 29 dB and high front‐to‐back ratio of more than 26 dB at the operating frequencies. The measured peak gain is 17.9 and 18.1 dBi for the lower and upper bands, respectively, and the cross polarizations isolation (CPI)(within ±60º of the mainlobe) is 16 dB lower than the broadside co‐polarization. It was confirmed that the proposed antenna array meets the communication standards in China. © 2015 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:154–163, 2016.